ANALISIS FINANCIAL DISTRESS DENGAN METODE ALTMAN, ZMIJEWSKI, GROVER, SPRINGATE, OHLSON DAN ZAVGREN UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN RITEL - Fahma, Yoga Taufan; Setyaningsih, Nina Dwi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
Financial distress is a condition of the company's financial performance which is marked by a decline in the company's net profit and the difficulty of the company paying short-term obligations and long-term obligations. This if allowed to drag on will cause the company to go bankrupt. There are various methods to predict company bankruptcy, namely the Altman, Zmijewski, Grover, Springate, Ohlson, and Zavgren methods. The purpose of this thesis is to determine the accuracy of financial distress analysis from various methods to predict bankruptcy.The research used is quantitative research with a descriptive approach. The statistical analysis in this study uses the calculation of the company's financial ratios from each bankruptcy method, while the hypothesis test uses accuracy and type of error. The results of this study indicate that the Altman method has an accuracy of 80%. The Zmijewski method has an accuracy of 60%. The Grover method has an accuracy of 80%.The Springate method has an accuracy rate of 70%. Ohlson's method has an accuracy of 90%. The Zavgren method has an accuracy of 100%. From these results it can be concluded that the Zavgren method is the most accurate in predicting bankruptcy in Retail companies.